PENINGKATAN HASIL BELAJAR SISWA MELALUI PENDEKATAN PEMBELAJARAN BERDIFERENSI DI SEKOLAH DASAR 100/II MUARA BUNGO - Umi Fauziah; Kurniawan , Sugeng; Maulani, Revi; Ulfa; Fadli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the improvement of students’ mathematics learning outcomes on the topic of three-dimensional shapes through the implementation of a differentiated learning approach in Grade IV students of SD Negeri 100/II Muara Bungo. The study employed a quantitative approach using a One Group Pretest–Posttest Design. The research subjects consisted of 20 fourth-grade students. Data were collected through tests, observations, and documentation. The tests were administered in the form of a pretest and posttest to measure students’ learning outcomes before and after the implementation of differentiated learning.The data were analyzed using descriptive statistics and a Paired Sample t-Test.The results showed that the implementation of differentiated learning significantly improved students’ learning outcomes. The mean pretest score increased from 54.5 to 82.25 on the posttest. In addition, the learning mastery level improved from 0% to 100%. The t-test analysis revealed that the calculated t-value (9.00) was greater than the critical t-value (2.262) at the 0.05 significance level, indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted.Therefore, it can be concluded that the differentiated learning approach is effective in improving mathematics learning outcomes on the topic of three-dimensional shapes among Grade IV students at SD Negeri 100/II Muara Bungo.